RETRACTED: Protecting the Rights of Minorities under International Law and Implications of COVID-19: An Overview of the Indian Context - Nehaluddin Ahmad (Laws)
The concept of majority rule and respect for minority rights is demonstrated in several constitutions of the world. Oppression by the majority of the minority is barred by articles of these respective constitutions. Today, democracy is mostly a method of government of the people that is ruled by the people. The issue of minority rights is at the center of the concept of civic rights. Minority protection, thus, operates on the hypothesis that religious, cultural, and linguistic affiliations are essential features of the very notion of a civic, just society. This paper offers an alternative account of why minority rights have international significance and more information on the value of an international, socially just process for the allocation of resources by states. By this approach, international minority rights speak to the wrongs that international law itself produces by organizing international political reality into a legal order. This article focuses on the uncertain effect of religious autonomy in India and the outcome of democracy in the country. While the Indian constitution guarantees autonomy to its religious minorities and promises minorities their freedoms, Indian democracy, which was once considered remarkable in scale and duration, has been weakened by the rise of xenophobic nationalism and threats to religious minorities. Even the safety and religious freedom of minorities have been compromised during COVID-19. In the last few decades, these trends have been clear; however, they have dramatically increased in the last few years, and the administration has turned a blind eye.